2017
DOI: 10.1111/aas.13018
|View full text |Cite
|
Sign up to set email alerts
|

Insertion methods comparison for The Streamlined Liner of the Pharynx Airway in children by novice

Abstract: The 120° bend improved SLIPA insertion when performed by novice, as reflected by higher insertion success rates and shorter insertion times, with no statistical differences in hemodynamic response to insertion or the incidence rates of complications between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Our study showed that the SLIPA-3G had a similar insertion time, success rate and fiberoptic views as the LMAS in the hands of experienced anesthesiologists. Previous studies have found that the SLIPA is easier to insert for novices compared to other conventional SADs [ 18 20 ]. The SLIPA may therefore be useful as a rescue airway in resuscitation scenarios, where the operator may not be an anesthesiologist or have much experience with the insertion of SADs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the SLIPA-3G had a similar insertion time, success rate and fiberoptic views as the LMAS in the hands of experienced anesthesiologists. Previous studies have found that the SLIPA is easier to insert for novices compared to other conventional SADs [ 18 20 ]. The SLIPA may therefore be useful as a rescue airway in resuscitation scenarios, where the operator may not be an anesthesiologist or have much experience with the insertion of SADs.…”
Section: Discussionmentioning
confidence: 99%